Practices of Family Health Professionals Regarding Chronic Disease Control and Prevention Programs - Kabasakal, Esma; Kublay, Gulumser (Suamthi Publications, 2017)
Introduction: Chronic diseases are of the utmost importance, due to their impact on high death rates, excessive increases in health expenses, and sustainability of health services. Further, it is recommended for individuals, and society at large, to decrease exposure to modifiable risk factors, like tobacco use, malnutrition, and lack of physical activity, and to encourage a lifestyle that supports the fight against chronic diseases. The aim of this study was to determine the practices of health professionals in terms of preventing chronic diseases and improving health. Methods: Health professionals from family health centers participated in this survey study. The data collection tool was developed by the researcher, by considering the nationwide health programs applied in Turkey, namely the Tobacco Control Program, Healthy Nutrition and Active Life Program, Turkey Diabetes Prevention and Control Program, and Cancer Control Programs. Results: Those who received training on health promotion had higher rates of involvement in tobacco cessation guidance, directing individuals to smoking cessation centers, giving trainings to cancer patients and others at risk, following up on individuals with a risk of obesity, raising awareness of healthy individuals concerning obesity, and training patients/patient relatives on diabetes. Discussion: The level of training that health professionals offer to patients and their relatives is higher than the level of training given to healthy individuals in all control programs. This inclination is an indicator of a treatment-oriented service approach to health. The capacity of health professionals should be directed more towards preventive medicine and health improving practices.
Keywords: Family Health Center; Chronic diseases; Control and prevention programs